Genetic mapping of a Urochloa interspecific mapping population for spittlebug resistance - Espitia Buitrago, Paula; de Vega, José; Jauregui, Rosa (2024)
This report presents the progress made in collaboration with the Earlham Institute to identify QTL associated with spittlebug nymph (Aeneolamia varia) resistance in a Urochloa interspecific mapping population. Previous efforts focused on using polyploid-specific software tools for genetic mapping (Espitia-Buitrago et al., 2022, 2023). However, despite resequencing to increase the read depth of RAD sequencing reads, challenges remain in accurately calling allele dosages and calculating recombination fractions between marker pairs. These difficulties are reflected in the limited number of simplex markers available, which are crucial for implementing the outbred F1 workflow proposed by Maliepaard et al. (1997).